2010
DOI: 10.1002/pssc.200982956
|View full text |Cite
|
Sign up to set email alerts
|

Ion irradiation of multi‐walled boron nitride nanotubes

Abstract: Multi‐walled boron nitride nanotubes were irradiated with low and medium energy argon and helium ions at room and elevated temperatures. The irradiated samples were characterized by transmission electron microscopy and Raman spectroscopy, and a comparison to the response of carbon nanotubes to irradiation was made. A dose of 2 × 1015 ions/cm2 was found to give rise to complete amorphization for irradiation with 40 keV Ar ions,while a comparable dose (in terms of displacement per atom) of 1.2 × 1018 ions/cm2 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Similar changes in the Raman lineshape have been reported for GaN [47] and diamond with varying crystal sizes [48].We therefore attribute the new Raman feature to nc-BN. This implies that at this fluence the effect of irradiation is to induce amorphization due to increased stress in the sample.The fluence dependence of the formation of nc-BN has been observed in previous work for B and other ions with the threshold fluence for nucleation for B implantation being in the order of 10 15 ions/cm 2 [44], [50].Other studies have also shown that c-BNwas not detected at fluences of the order if 10 18 ions/cm 2 with h-BN as a starting material [24,51].…”
Section: Haadf-stem and Hrtemsupporting
confidence: 65%
“…Similar changes in the Raman lineshape have been reported for GaN [47] and diamond with varying crystal sizes [48].We therefore attribute the new Raman feature to nc-BN. This implies that at this fluence the effect of irradiation is to induce amorphization due to increased stress in the sample.The fluence dependence of the formation of nc-BN has been observed in previous work for B and other ions with the threshold fluence for nucleation for B implantation being in the order of 10 15 ions/cm 2 [44], [50].Other studies have also shown that c-BNwas not detected at fluences of the order if 10 18 ions/cm 2 with h-BN as a starting material [24,51].…”
Section: Haadf-stem and Hrtemsupporting
confidence: 65%
“…The only experiment, 492 which was recently carried out, indicated that BN MWNTs subjected to 40 keV Ar + ion beam are amorphized at irradiation doses of ϳ10 15 cm −2 ͑Fig. 63͒ and that the amount of damage can be considerably reduced if the sample is kept at elevated temperatures ͑600°C.͒ The irradiation dose at which amorphization occurred corresponded to ϳ2.5 dpa, which is close to the values typical for the amorphization of carbon nanotubes.…”
Section: B Ion Irradiationmentioning
confidence: 51%
“…Synthesis of c-BN has been found to be of interest because of its excellent physicochemical properties, some of which are superior to those of diamond [1,2]. Hexagonal BN also exhibits extreme properties especially where thermal stability and chemical inertness are concerned [3,4]. The production of a thin film c-BN layer on h-BN surface would have advantages in combining the properties of both materials.…”
Section: Introductionmentioning
confidence: 99%